Barriers To utilization of oral health care services among antenatal mothers in Kuantan, Pahang - Abllah, Zurainie; Abd. Aziz, Karimah Hanim; Jamani, Nurjasmine Aida (2017)
During pregnancy, increased acidity in the mouth increases the risk of antenatal mother to get dental caries. It is worsen if antenatal mother has morning sickness like vomiting during pregnancy. It can aggravate the problem by exposing the teeth to more gastric acid. In addition, antenatal mothers have hormonal changes that they are more susceptible to periodontal problems. Therefore, it is important for antenatal mother to get dental treatment and use oral health service. This study aim is to describe barriers to utilisation of oral health care services among antenatal mothers attending the Klinik Kesihatan Ibu dan Anak around Kuantan. Materials and Methods: A cross sectional study which was conducted among purposely selected 296 antenatal mothers aged 18-45 years from Kuantan, Pahang in 18 months duration. Study used validated self-administered questionnaire to obtain information on the variables of interest. Results: Common barriers to utilization of services among antenatal mothers are fear to dental pain (45.6%), time constraints- busy at workplace (36.5%) and feeling of not having any dental problems (36.1%). Meanwhile the least barrier to oral health care services among antenatal mothers is attitude of the dentist (0.7%), followed by attitude of the staff (1.4%) and condition of treatment room (1.7%) Conclusion(s): Fear of dental pain is the main barrier to utilization of service among antenatal mothers and dissatisfaction of the service provided is the least barrier among other factors.